KOMUNKASI ISlAM QURBAN DAN PENSVARlATANNYA - Muhtadin, Muhtadin (Universitas Prof. Dr. Moestopo (Beragama), 2008)
Generally speaking, communcation can be defined as an effort to intluence. invite and tranfer thought, ideology, knowledge and acts to others so that they want to observe our thought, ideology, knowledge or acts. Meanwhile, communication of Islam is to invite or to tranfer or to impeiemnt Islamic ideas, or to persuade others to give up what is forbidden by god and to what is commanded by him.A.Hasyami says that communication in Islam is a call for believing in and impiementinq Islamic Sharia. Sim!larly, Prof Tone Yahya Umar, MA maintains that communication of Islam a religious call through persuasion education, or teechinq. Thus, Islamic communication as a religious call has a broad and complex meaning.In Islam, sacrifice is slaughtenng sacrificial animals (camel, cow and sheep) in 10, 11, 12, or 13 of Dzulh!Jjah intended to get closer to God Islam commands its followers to do the sacrifice as one of religious rites. However, based on Ouren and hadits, Mus/tin scholars have two different opinions on the status of sacrifice in Islam :1. Wajib, for those able to sacrifice2. Sunat muakkad, for able to sacrificeMeanwhile, for those who has passed aways, Muslim scholars state state that the sacrifice is allowed with the following conditions:1. it involves those stilt alive2. the sacrifice is carried out forparticular will of the death3. the sacrifice for the death is categorized as sadaqa (religious alms)Neverheless, this kind of sacrifice (for the death) has never been practiced by the Prophet Muhammad, Peace be upon him.